Establishment and evaluation of a carotid artery dissection model in rats - Zhang, Shufan; Han, Zhenxiang; Cao, Ying; Wu, Weicheng; Liu, Yuanzeng; Yang, Shilin; Feng, Xiaochao; Yu, Chun; Zhu, Zhu; Dong, Qiang; Han, Xiang (Frontiers in Neurology, 2024)
BackgroundGiven the lack of models for carotid artery dissections (CAD), we aim to investigate effects of beta-aminopropionitrile (BAPN) combined with physical damage on the arterial walls of rats, and to establish a high-incidence and low-mortality CAD model.MethodsSixteen SPF SD rats (3-week-old) were divided into two groups. Group B was given 0.25% BAPN solution and group W was given water. Then we established an animal model of CAD by carotid artery torsion. One of the two carotid arteries in each rat was randomly selected for torsion. We got four groups of blood vessels following above-mentioned methods: BAPN plus torsion group (group Bt), BAPN plus non-torsion group (group Bn), water plus torsion group (group Wt), and water plus non-torsion group (group Wn). The hematoxylin and eosin (HE) staining and Verhoeff’s Van Gieson (EVG) staining were performed to observe structures of arteries. Immunofluorescence staining was used to detect structural proteins in vessels. We used triphenyltetrazolium chloride (TTC) staining and neurological function assessment to detect the infarct area of brain and neurological deficits in rats with carotid dissection to verify the validity of the rat model.ResultsBAPN treatment significantly affected the weight gain of rats, but had little effect on survival during the first 5 weeks. The group Bt had the highest incidence of CAD among all groups (p = 0.014). HE staining of carotid artery tissue sections showed that the vascular walls were the thickest in group Bt (p < 0.001). EVG staining showed the arrangement of elastic fibers was the most irregular in group Bt. Immunofluorescence staining revealed that the expression of a-SMA and SM22a were decreased remarkably in group Bt (p < 0.001). Both motor and sensory deficits were more severe in CAD group than control group (p = 0.0004; p = 0.0036). The relative infarction volumes of CAD group rats were significantly larger than control group (p < 0.001).ConclusionThe animal model of CAD can be feasible to establish by mechanical torsion combined with BAPN free drinking. With this method, the animal mortality was low and the model formation rate was high. This model will enable further studies on CAD.